2008
DOI: 10.1038/bjp.2008.114
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone and the autocrine modulation of potassium currents and oxidative stress in the diabetic rat heart

Abstract: Background and purpose: Aldosterone plays a major role in cardiac pathology. This study was designed to investigate the role of cardiac aldosterone in modulating K þ currents and oxidative stress in the streptozotocin-induced diabetic rat heart. Experimental approach: Transient and sustained K þ currents were measured in ventricular myocytes by voltage clamp. Plasma and cellular aldosterone were measured by ELISA. Fluorescent dihydroethidium (DHE) was used to assess superoxide ions as markers of oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 74 publications
(172 reference statements)
1
18
0
Order By: Relevance
“…A physiological increase in serum aldosterone concentration in response to restriction in sodium intake does not affect I Ca,L , I to and action potential duration in the rat left ventricle in vivo. Shimoni et al 2008 In streptozotocin-induced diabetic rat heart, spironolactone augments I to in diabetic males (with a concomitant shortening of action potential duration) but has no effect in diabetic female animals.…”
Section: Wagner Et Al 2008mentioning
confidence: 98%
See 2 more Smart Citations
“…A physiological increase in serum aldosterone concentration in response to restriction in sodium intake does not affect I Ca,L , I to and action potential duration in the rat left ventricle in vivo. Shimoni et al 2008 In streptozotocin-induced diabetic rat heart, spironolactone augments I to in diabetic males (with a concomitant shortening of action potential duration) but has no effect in diabetic female animals.…”
Section: Wagner Et Al 2008mentioning
confidence: 98%
“…Even more complicated seems to be a genderrelation and sex-hormone dependence of I to alteration by aldosterone or MR antagonism: in streptozotocin-induced diabetic rat heart, spironolactone augmented I to in diabetic males (with a concomitant shortening of action potential duration) but had no effect in diabetic female animals. Effects of spironolactone were restored in ovariectomized diabetic females and abolished in orchidectomized diabetic males (Shimoni et al 2008). Boixel et al (2006) showed that incubation of isolated adult mouse ventricular myocytes with aldosterone resulted in a significant increase of cardiac sodium current I Na (without alterations of the biophysical properties) which was prevented by co-incubation with spironolactone.…”
Section: Costa Et Al 2009mentioning
confidence: 99%
See 1 more Smart Citation
“…44 There may be sex differences in the mediation of glucose regulation by stress response, and glucocorticoid stress might also play a more relevant role in development of DM in male rodents. 45 …”
Section: Animal Modelsmentioning
confidence: 99%
“…Both bradycardia and malignant ventricular arrhythmias occur in diabetic subjects (5,6). Prolongation of the action potential duration leading to myocardial electrical instability predisposes the heart to rhythm disturbances and is considered to be a main feature of cardiac dysfunction of diabetic subjects (7)(8)(9)(10). In addition, the diabetic heart is characterized by an early asymptomatic left ventricular diastolic dysfunction followed by late systolic dysfunction (11,12).…”
Section: Introductionmentioning
confidence: 99%